The Effects of Intranasal Oxytocin on Neural and Behavioral Responses to Social Touch in the Form of Massage - Chen, Yuanshu; Li, Qin; Zhang, Qianqian; Kou, Juan; Zhang, Yingying; Cui, Han; Wernicke, Jennifer; Montag, Christian; Becker, Benjamin; Kendrick, Keith M.; Yao, Shuxia (Frontiers in Neuroscience, 2020)
Manually-administered massage can potently increase endogenous oxytocin concentrations and neural activity in social cognition and reward regions and intranasal oxytocin can increase the pleasantness of social touch. In the present study, we investigated whether intranasal oxytocin modulates behavioral and neural responses to foot massage applied manually or by machine using a randomized placebo-controlled within-subject pharmaco-fMRI design. 46 male participants underwent blocks of massage of each type where they both received and imagined receiving the massage. Intranasal oxytocin significantly increased subjective pleasantness ratings of the manual but not the machine massage and neural responses in key regions involved in reward (orbitofrontal cortex, dorsal striatum and ventral tegmental area), social cognition (superior temporal sulcus and inferior parietal lobule), emotion and salience (amygdala and anterior cingulate and insula) and default mode networks (medial prefrontal cortex, parahippocampal gyrus, posterior cingulate and precuneus) as well as a number of sensory and motor processing regions. Both neural and behavioral effects of oxytocin occurred independent of whether subjects thought the massage was applied by a male or female masseur. These findings support the importance of oxytocin for enhancing positive behavioral and neural responses to social touch in the form of manually administered massage and that a combination of intranasal oxytocin and massage may have therapeutic potential in autism.